Vacuous Names in Early Analytic Philosophy: Frege, Russell, and Moore. Issue 6 (June 2016) - Textor, Mark
Abstract: Empty proper names give rise to intriguing questions. Frege, Moore and Russell stand at the beginning of analytic philosophy's engagement with these questions. In this paper I will therefore introduce and assess their views on the topic of empty names and draw connections to recent work.